Systemic antifungal strategies in allogeneic hematopoietic stem cell recipients hospitalized in french hematology units: a post-hoc analysis of the cross-sectional observational AFHEM study﻿ - Mauricette Michallet; Jean El Cheikh; Raoul Herbrecht; Ibrahim Yakoub-Agha; Denis Caillot; Jean-Pierre Gangneux (BMC Infectious Diseases, 2022)
Abstract Background Invasive fungal diseases (IFD) remain a major complication of allogeneic hematopoietic stem cell transplantation (alloHSCT) and are associated with high mortality rates in patients receiving alloHSCT. Antifungal prophylaxis is increasingly being used in the management of IFDs in patients receiving alloHSCT. Methods A post-hoc analysis of the cross-sectional observational AFHEM study was carried out to describe the use of antifungal drugs in real-life clinical practice in alloHSCT recipients hospitalized in French hematological units. Results A total of 147 alloHSCT recipients were enrolled; most were adults (n = 135; 92%) and had received alloHSCT < 6 months prior to enrollment (n = 123; 84%). Overall, 119 (81%) patients received a systemic antifungal therapy; of these, 95 (80%) patients received antifungal prophylaxis. Rates of patients receiving systemic antifungal treatment were similar irrespective of transplant time, neutropenic, and graft-versus-host disease status. Among patients on systemic antifungal treatment, 83 (70%) received an azole, 22 (18%) received an echinocandin, and 16 (13%) received a polyene. Conclusions This work provides evidence of the antifungal strategies used in alloHSCT recipients hospitalized in French hematological units. Unlike earlier studies, the AFHEM study showed that prophylaxis appears to be the leading antifungal strategy used in alloHSCT recipients in France.